PENGUKURAN EFEKTIVITAS MESIN PRODUKSI BUBBLE WRAP MENGGUNAKAN METODE OVERALL RESOURCE EFFECTIVENESS Studi Kasus PT GMP Sukses Makmur Indonesia - Kuncoro Adhi Gautama; Widya Setiafindari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
PT GMP Sukses Makmur Indonesia is a company engaged in the production of Bubble Wrap (bubbled plastic). This company produces 818,680 rolls with an average monthly production of 68,223 rolls. The problem that often arises at Pt Gmp Sukses Makmur Indonesia is the high production machine delay time with a downtime of 705.43 hours and a breakdown of 663.33 hours in one year, so the engine performance is less effective. This can lead to not achieving production targets which cause losses. The purpose of this study is to determine the effectiveness of the Bubble Wrap production machine using the Overall Resource Effectiveness (ORE) measuring tool and to find the causes of the problems that have been carried out using the ORE method on Bubble Wrap production machines during the period September 2021 – August 2022. ORE is a method that is useful in measuring the effectiveness of production time by taking into account the resources which include humans, machines, materials and methods. In the ORE method there are seven factors that are measured including readiness, availability of facility, changover efficiency, availability of material, availability of manpower, performance efficiency, dan quality rate. The results of measuring machine effectiveness using the Overall Resource Effectiveness (ORE) method for Ektruder machines were 76.41%, Crushers 99.59%, Cooling 98.99%, Mixers 99.79%, and Air Compressors 98.88%. Based on the method used, it is known that in the Bubble Wrap production process, the extruder machine does not meet the ORE standard of 85%, while the influencing factors are performance efficiency and quality rate. where the value of performance efficiency and Quality rate does not meet the standard so that it affects the high value of Overall Resource Effectiveness (ORE).